y = Cb

^{x}Since (0,-2) is on the graph, -2 = Cb

^{0}. So, C = -2.Therefore, y = -2b

^{x}Since (1,-6) is on the graph, -6 = -2b

^{1. }So, b = -6/(-2) = 3Thus, y = -2(3)

^{x}Katie V.

asked • 12/04/16Determine an exponential function in the form y=Cb^{x} given two points (0,-2) and (1,-6)

the answer is y= -2(3^{x}) but I do not know how that was reached

thank you in advance

Follow
•
2

Add comment

More

Report

y = Cb^{x}

Since (0,-2) is on the graph, -2 = Cb^{0}. So, C = -2.

Therefore, y = -2b^{x}

Since (1,-6) is on the graph, -6 = -2b^{1. }So, b = -6/(-2) = 3

Thus, y = -2(3)^{x}

Ask a question for free

Get a free answer to a quick problem.

Most questions answered within 4 hours.

Find an Online Tutor Now

Choose an expert and meet online. No packages or subscriptions, pay only for the time you need.